Agroforestry land use strategies for the ecological conservation and agricultural development of upland areas in Dinalupihan, Bataan - Chua, Lawrence Angelo U. (School of Urban and Regional Planning,University of the Philippines Diliman, 2019)
Forest and upland areas, although very prevalent in the Philippines, have very fragile ecosystems in terms of their capacity to adjust to excessively exploitive human activities. Forest and upland ecosystems provide multitudes of ecosystem services to their inhabitants, inclusive of humans who subsist on their bounties. The upland areas of the Municipality of Dinalupihan are characterized by the following land uses: (a) 18% to 30% slope of diversified croplands; (b) 30% to 50% slope for plantation/orchard and pasture; and (c) more than 50% slope for forest or wood lots. These land uses of the upland areas make them moderately and highly suitable to agroforestry, eco-tourism, pastural, and subsistence extraction activities. The assessment of the social and economic values indicated that in terms of provisioning ecosystem services, agroforestry helps farmers increase crop and timber production as well as expand their source of income. In therms of cultural ecosystem services, agroforestry increases circulation of people who visit the place for aesthetic, recreational, and heritage purposes. Lastly, agroforestry is considered as the most productive activity in terms of the economic value of land uses in the upland areas. The identified spatial strategies for agroforestry are to include the agroforestry overlay zone, forest buffer overlay zone, and the the One-Town-One-Product (OTOP) overlay zone in the Zoning Ordinance. This will serve as guides in the development of the upland areas of the Municipality of Dinalupihan into sustainable agroforestry systems, and; in boosting the environmental conservation and agricultural development in the upland areas. To carry out theses strategies, the following are recommended: a) promotion of sustainable agroforestry by the LGU; b) development of community and partnership building programs between the public and private organizations; and c) developmemt of institutional capacity building programs.